2020
DOI: 10.30901/2658-3860-2019-3-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Genus Allium L. (Alliaceae) in Siberia

Abstract: The genus Allium in Siberia has been revised. The materials of LE, WIR, MW, ALTB, NSK, OSBU herbarium collections, information resources on the Internet, literature data on the flora of various regions of Russia and neighboring states, as well as materials personally gathered during collecting missions have been analyzed. As a result, it was established that 62 Allium species grow in Siberia, of which 11 are endemic. The synopsis presented in the article reflects the modern system of the genus Allium. The info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Consequently, the occurrence of A. strictum from peninsular Italy should be excluded. This latter species is very rare in Italy, where it occurs only in the Alps, representing the western limit of its distribution area (e.g., [ 9 , 12 , 19 , 29 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the occurrence of A. strictum from peninsular Italy should be excluded. This latter species is very rare in Italy, where it occurs only in the Alps, representing the western limit of its distribution area (e.g., [ 9 , 12 , 19 , 29 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The latter section is characterized by sub-conical bulbs inserted above a short rhizome, with reticulated tunics and linear, flat leaves [ 4 , 17 ]. Allium strictum is a Eurasian species distributed in Europe, Russia, Kazakhstan, Kyrgyzstan, Mongolia and China [ 12 , 18 , 19 ]. Some authors (e.g., [ 13 , 20 ]) have highlighted the uncertain systematic position of the Apennines’ populations of A. strictum , suggesting further study.…”
Section: Introductionmentioning
confidence: 99%
“…Bartolucci et al identified A. ducissae , a new breed of Allium that grows in the mountainous regions of the Central Apennines in the Abruzzo and Lazio counties of Italy [ 113 ]. Furthermore, A. strictum , a Eurasian species, is distributed across China, Europe, Russia, Kazakhstan, Kyrgyzstan, and Mongolia [ 114 , 115 ]. A. umbilicatum , also called gladiolus or leek is usually localized in semi-arid regions and can tolerate sub-zero freezing winters [ 116 ].…”
Section: The Genus Alliummentioning
confidence: 99%